Propriedades clássicas e quânticas do campo eletromagnético associado a um biofóton - Marques, Jamylle da Costa (2024)
Biophoton is an electromagnetic radiation emitted by biological systems. It consists of waves packet carrying informational value, capable of modulating the physiological activities of cells and living systems. When comparing the theoretical results of photon emission from a chaotic thermal field and a completely coherent field with experimental data, there are indications that biophotons originate from coherent fields occurring in living tissues. In order to investigate further information about this topic, a classical and quantum description was performed, considering the biophoton’s Hamiltonian and using Maxwell’s equations and classical time-dependent dynamic invariants. Additionally, an investigation was conducted regarding the relationship between coherent states and the biophoton system. This approach allowed for the exploration of electromagnetic dynamics of biophotons to verify that the electromagnetic fields do not decay exponentially and how coherent states are intrinsically related to the biophoton system. In this sense, considering the scientific importance of the biophotons and quantum invariants, not only in physics but also in various areas of knowledge, the investigation of their properties through the aforementioned methods could contribute to knowledge on the subject, generating applicability in various fields and consequently contributing to the advancement of science and its technologies.